UPAYA KASI PENDIDIKAN AGAMA DAN KEAGAMAAN ISLAM DALAM PEMBINAAN KINERJA PENGAWAS PAI DI KEMENTERIAN AGAMA KABUPATEN KAUR - Hendri Dunan (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2017)
Abstract: The results of the analysis of the data showed that: 1. Efforts Kasi Islamic Religious Education and Religious Affairs in the Development of Supervisory Performance of Islamic Education in the Ministry of Religious Kaur District: a) Strive for the performance of supervisory activities in the promotion of Islamic education to be incorporated into the budget. b) Attempts to monitoring and evaluation of Islamic Schools Supervisors should be done regularly, and if necessary the fore implemented a reward system performance. c) regularly programmed activities that can support the promotion of academic competence of professional supervisors. d) encourage and facilitate supervisors to participate in supervisory activities. e) Supervision of Islamic Education required a fingerprint in the nearby Religious Affairs Office. f) Every single week of Islamic Education Compulsory supervisors provide supervisory reports. g) At the time of two months, provide guidance to supervisors of Islamic Education to monitor the progress and obstacles in the learning of Islamic Education teachers in the school. 2. Factors hindering the Head of Religious Education and Religious Islam in fostering supervisory Islamic Education at the Ministry of Religious Affairs Kaur District: a) Supervision of Islamic Education in the District Kaur is still lacking, Number of Islamic Schools Supervisors two people, while the number of schools to 152 schools monitored. b) There is no budget for facilities and infrastructure in fostering supervisory absence of which the motor vehicle department and a special room supervisor Islamic Education so that the lack of awareness of the functions, basic tasks, authority and responsibility in carrying out the regulatory performance of Islamic Education.